استخدام لعبة المونوبولي في ترقية كفاءة المفردات - Nur Aini Majidah (Abjadia, 2017)
إ المفردات هي واحدة من العناصر الهامة للغة. يتطلب تعلم المفردات وسائل تعليمية لإثراء المفردات. تعلم المفردات في مدرسة هداية المبتدئين الثانوية مالانج يستخدم الكتب فقط حتى يشعر الطلاب بالملل. تستخدم هذه الدراسة نهجًا كميًا باستخدام صيغة "t test" لتحليل البيانات. هذا النوع من الأبحاث عبارة عن تجربة تتكون من مجموعتين: التحكم والتجربة. تستخدم أداة جمع البيانات المراقبة والمقابلات والاختبارات والتوثيق. تظهر النتائج أن اللعب الاحتكاري (المونوبولي) فعال لتحسين إتقان المفردات. يمكن أن نرى من مقارنة قيمة النشرات من مجموعة التحكم والتجريبية، أن نتيجة اختبار t في هذه الدراسة (4.29) ، أكبر من قيمة اختبار t عند مستوى 1٪ (2.42) و 5٪ (2.68).Vocabulary is one of the important elements of language. Vocabulary learning requires learning media to enrich vocabulary. Vocabulary learning in MTs Hidayatul Mubtadi'in Malang only uses books so students feel bored. This study uses a quantitative approach using the formula "t test" to analyze the data. This type of research is an experiment consisting of two groups: control and experiment. The data collection instrument uses observation, interviews, tests and documentation. The results show that monopoly play is effective for improving vocabulary mastery. It can be seen from the comparison of postes value from the control and experimental group, that the result of t test in this study (4.29), is greater than the value of t test at the level of 1% (2.42) and 5% (2.68 ).